2018
DOI: 10.1177/2158244017754238
|View full text |Cite
|
Sign up to set email alerts
|

What Do You Mean, “What Does It All Mean?” Atheism, Nonreligion, and Life Meaning

Abstract: Nonreligion is often thought to be commensurate with nihilism or fatalism, resulting in the perception that the nonreligious have no source of meaning in life. While views to this effect have been advanced in various arenas, no empirical evaluation of such a view has been conducted. Using data from the 2008 American General Social Survey (N = ~1,200), we investigated whether atheists, the religiously unaffiliated, and persons raised religiously unaffiliated were more likely than theists, the religiously affili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 52 publications
1
21
0
Order By: Relevance
“…When atheists are disaggregated into different worldview "types," some types closely resemble the religious [70]. Moreover, in a nationally representative U.S. sample using self-reported fatalistic and nihilistic attitudes to THE PSYCHOLOGY OF NONBELIEVERS 11 indicate the lack of personalized meaning, Speed, Coleman, and Langston [72] found no differences between self-identified believers and nonbelievers or being raised in a religious vs. a nonreligious household. Although further research is necessary to untangle the hows, whens, and whys the nonreligious and religious may differ on meaning in life, the research reviewed above challenges the idea that nonreligiosity entails a "meaning gap" or that the meaning in life experienced by nonbelievers qualitatively differs from that experienced by believers.…”
Section: Example Of the (Non)religion-health Curvilinear Relationshipmentioning
confidence: 99%
“…When atheists are disaggregated into different worldview "types," some types closely resemble the religious [70]. Moreover, in a nationally representative U.S. sample using self-reported fatalistic and nihilistic attitudes to THE PSYCHOLOGY OF NONBELIEVERS 11 indicate the lack of personalized meaning, Speed, Coleman, and Langston [72] found no differences between self-identified believers and nonbelievers or being raised in a religious vs. a nonreligious household. Although further research is necessary to untangle the hows, whens, and whys the nonreligious and religious may differ on meaning in life, the research reviewed above challenges the idea that nonreligiosity entails a "meaning gap" or that the meaning in life experienced by nonbelievers qualitatively differs from that experienced by believers.…”
Section: Example Of the (Non)religion-health Curvilinear Relationshipmentioning
confidence: 99%
“…Compared to the religious, there is evidence that atheists are more open to experience, less dogmatic, favor analytic thinking styles over intuitions, demonstrate lower social conformity, and have specific interests in the sciences (Bainbridge 2005;Caldwell-Harris 2012;Farias 2013). Moreover, atheists are more likely to report that meaning in life is purely selfconstructed, and they do not appear to suffer any existential penalties for this such as nihilistic or fatalistic outlooks (Speed, Coleman, and Langston 2018) nor do they report more 'crises of meaning' (Schnell and Keenan 2011). Far from being the paragons of cold logic and rationality, however, qualitative studies have suggested atheists experience deeply moving moments of profundity and transcendence.…”
Section: Exploring Atheismmentioning
confidence: 99%
“…Researchers have long known that the development of meaning in life is associated with positive physical (Reker, Peacock, & Wong, 1987;Czekierda, Banik, Park & Luszczynska, 2017) and mental health outcomes (Schnell, 2009;Zika & Chamberlain, 1992). Several studies have found either no differences or comparable levels of meaning in life between atheists and theists (Caldwell- Harris et al, 2011;Speed, Coleman, & Langston, 2018;Wilkinson & Coleman, 2010), which suggests atheists draw on other sources of meaning than those traditionally afforded by religion. Nevertheless, in one recent study, atheists were slightly more likely than theists to report statements that life has no objective meaning.…”
Section: Meaning In Lifementioning
confidence: 99%